Respuestas

2013-09-08T21:54:46+02:00
Fatty,

x(x + 3) = 270
x^2 + 3x = 270
x^2 + 3x - 270 = 0
            delta = 3^2 - 4.1.(-270) = 1089          raiz = 33
x = 1/2(- 3 + - 33)
   x = - 36/2                             x1 = -18
   x = 30/2                               x2 = 15
                                                              S = {- 18, 15}

2013-09-08T22:18:05+02:00
X(x+3) = 270
x^2 + 3x = 270
x^2 + 3x - 270 = 0
(x-18)(x+15) = 0
x = 18
x = -15


a^2 + a = 132
a^2 + a - 132 = 0
(a-11)(a+12) = 0
a = 11
a = -12


3n^2 - n = 102
3n^2 - n - 102 = 0
9n^2 - 3n - 306 = 0
(3n-18)(3n+17) = 0
3n -18 = 0
3n = 18
n = 6
3n+17 = 9
3b = -17
n = -17/3